A low-power monolithic three-axis accelerometer with automatically sensor offset compensated and interface circuit. (April 2019) - Yeh, Chih Yuan; Huang, Jung Tang; Tseng, Sheng-Hsiang; Wu, Po-Chang; Tsai, Hann-Huei; Juang, Ying-Zong
Abstract: This work presents a monolithically integrated CMOS-MEMS three-axis capacitive accelerometer with an effective and practical method to compensate the sensor offset. By using correlated double sampling (CDS) and an automatic sensor offset compensated mechanism in the interface circuit, the purposes of low noise and low zero-gravity(zero-g) offset accelerometer are achieved. The zero-g offset compensated circuit calibrates the sensor offset in each axis. All of the calibrated procedure is executed automatically by a micro-control-unit (MCU). After calibration, the worst zero-g offset is reduced to ±50 mg and background calibration is no longer needed. The three-axis accelerometer was fabricated by using a 0.18-μm CMOS-MEMS process and the chip area containing the sensors and the integrated circuit is 2 × 2 mm 2 . It achieved a ±6 g sensing range and the noise was 350 μg/rtHz for the X- and Y-axes and Z-axes was 1.5 mg/rtHz with a total current consumption of 120 μA under 1.8 V.